2018
DOI: 10.1007/s11356-018-3186-5
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster as model organism for monitoring and analyzing genotoxicity associated with city air pollution

Abstract: This study evaluated the genotoxic potential of atmospheric pollution associated with urbanization using the model organism Drosophila melanogaster and the Comet assay with hemolymph cells. Larvae were exposed to atmospheric compounds in an urban and a rural area in the municipality of Vitória de Santo Antão, Pernambuco, Brazil, for 6 days (from the embryo stage to the third larval stage) in April 2015 and April 2017. The results were compared to a negative environmental control group exposed to a preserved ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Furthermore, the observed increases in RSPM and several toxic metals on the exoskeleton and internal tissues of field-collected bees using SEM-EDX suggest a direct relationship between exposure to RSPM and impacts on insect health and survival. Thus, to control for age, diet, source, and physiological differences between insects, we evaluated the survival, RSPM deposition, hemocyte levels, heart rate, and gene expression of laboratory-reared and age matched Canton Special D. melanogaster to laboratory conditions (C = control) as well as our low (L) and highly (H) polluted sites ( 66 ). Newly emerged flies ( n = 21,000, 7,000 flies/site, 1,000 flies per trial) were exposed for 10 d under similar shade and wind-protected locations and were provided with fresh food and water on alternate days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the observed increases in RSPM and several toxic metals on the exoskeleton and internal tissues of field-collected bees using SEM-EDX suggest a direct relationship between exposure to RSPM and impacts on insect health and survival. Thus, to control for age, diet, source, and physiological differences between insects, we evaluated the survival, RSPM deposition, hemocyte levels, heart rate, and gene expression of laboratory-reared and age matched Canton Special D. melanogaster to laboratory conditions (C = control) as well as our low (L) and highly (H) polluted sites ( 66 ). Newly emerged flies ( n = 21,000, 7,000 flies/site, 1,000 flies per trial) were exposed for 10 d under similar shade and wind-protected locations and were provided with fresh food and water on alternate days.…”
Section: Resultsmentioning
confidence: 99%
“…We separately used these same approaches to measure survival, circulatory physiology, and gene expression in laboratory-reared and age-matched D. melanogaster exposed to laboratory conditions and our low and highly polluted sites as described in ref. 66 for 10 d with food and water. Sample numbers, data assembly, measurements, and statistical analyses are described in SI Appendix , Materials and Methods .…”
Section: Methodsmentioning
confidence: 99%
“…Drosophila has been used to assess the toxicity of multiple sources of PM including tobacco smoke, coal combustion byproducts, and rural/urban ambient air samples ( Sadiq and Altaany, 2014 , Alija et al, 2016 ), de Santana et al, 2018 , Ruben et al, 2018 , Pandey et al, 2020 , Thimmegowda et al, 2020 ). Like in the other models, Drosophila studies assessed the impacts of whole PM, organic extracts, and water-soluble extracts ( Sadiq and Altaany, 2014 , Wang et al, 2017b , Pandey et al, 2020 ).…”
Section: Drosophila Melanogastermentioning
confidence: 99%
“…Interestingly, higher PM 2.5 exposure has been found to induce insulin resistance in humans according to Li et al (2017) and that elevated PM 2.5 levels were associated with higher prevalence of type 2 diabetes ( Liu et al, 2019 ). Genotoxicity from exposures to rural and urban PM were studied in fly larvae on site and through a Comet assay of Drosophila hemolymph (analogous to blood in vertebrates) cells exposed to ambient PM by de Santana et al (2018) , who found that urban PM significantly degraded Drosophila hemolymph DNA compared to rural and filtered air exposures, implicating metals (e.g, aluminum, silicon, sulfur, potassium, calcium, titanium, and iron) found in the urban samples. Injected cigarette smoke filtrate was also found to cause mutations during spermatogenesis of 2 to 3-day-old wild-type Drosophila by Sadiq and Altaany (2014 ), indicating that cigarette smoke may have greater genotoxicity than previously predicted.…”
Section: Drosophila Melanogastermentioning
confidence: 99%
“…Other invertebrate model organisms like D. melanogaster and C. elegans are also used for environmental monitoring. D. melanogaster in particular for assessing genotoxicity associated with air pollution (de Santana et al, 2018), nanotoxicity (Ong et al, 2015), nano‐genotoxicity (Carmona et al, 2015; Demir et al, 2015), and C. elegans in the identification of endocrine disrupting chemicals (EDS) in groundwater (Custodia et al, 2001), for monitoring bacterial air quality (Duclairoir Poc et al, 2011). These two invertebrate models have been in biological research for a long time and have been used extensively; however, silkworm has not been exploited to such an extent compared to them as it is in its initial stage of serving as a model.…”
Section: Silkworm B Mori As Antimicrobial Drug Screening and Pathogen...mentioning
confidence: 99%